UPAYA PENINGKATAN HASIL BELAJAR SISWA MENGGUNAKAN METODE BERMAIN PERAN MELALUI MODEL KOLABORATIF - Misniatun, Misniatun (Jurnal Pendidikan Guru, 2018)
This study aims to determine whether there is an increase in mathematics learning outcomes of students in before and after conducted research using Role Playing Methods Through Collaborative Model in third grade students of SD Negeri 20 Pekanbaru, which amounted to 31 students with 16 male students and 15 female students with heterogeneous (diverse) capabilities. For the sake of achieving the optimal learning objectives, efforts to improve the quality of learning must be continuously done. One of these efforts is by conducting classroom action research. Improved learning that is planned and done with the right formulation can reduce the emergence of IPS learning problems in class III about the wind is the lack of interest and practice of students because the methods and learning model is less fun because it is still classic because of many lectures. From these problems have an impact on the level of achievement of a low KKM. Therefore, the writer tries to improve this learning using process and classroom action research. The results of this study indicate that the number of students who reached KKM (78) in the initial data only 13 people (41%), cycle I as many as 19 people (61%), and cycle II 27 people (87%). The average student score at baseline was 69.3, cycle I increased to 76.7, then in cycle II increased again reached 84.2. Based on the results of this study it can be concluded that Role Playing Methods Through Collaborative Model can improve student learning outcomes in Mathematics students class III SD Negeri 20 Pekanbaru.